Practitioner Perspectives on Child Feeding in Uganda: Community Engagement through the Global Agenda - McBride, Amanda; Graham, Pamela Louise; Mugyisha, Alex; McInnes, Alison (Routledge, 2024)
This collaborative research study arose in response to the United Nations Sustainable Development Goals 2 and 3, which have amongst their targets an aim to eradicate preventable deaths in children under five years old. The research is founded on the aims of the Global Agenda for Social Work and Social Development which aims at strengthening the social work profession through linkages between global challenges and local responses. To address these issues through nutritious child feeding, it was essential to understand the views and experiences of SW and social development practitionersinvolved with child feeding practices. Through an online qualitative survey and reflexive thematic analysis, we explored the views and experiences of practitioners working with the Uganda Red Cross Society. Three themes were developed from analysis of the data: Lifestyle Choices & Restrictions; Limited Resources & Facilities; and Knowledge & Education. A reflection on the challenges encountered and advancing international social work through engagement with the Global Agenda are also presented.
Keywords: child feeding; global agenda; International Social Work; Uganda